2014
DOI: 10.5935/abc.20140089
|View full text |Cite
|
Sign up to set email alerts
|

Functional Vascular Study in Hypertensive Subjects with Type 2 Diabetes Using Losartan or Amlodipine

Abstract: BackgroundAntihypertensive drugs are used to control blood pressure (BP) and reduce macro- and microvascular complications in hypertensive patients with diabetes.ObjectivesThe present study aimed to compare the functional vascular changes in hypertensive patients with type 2 diabetes mellitus after 6 weeks of treatment with amlodipine or losartan.MethodsPatients with a previous diagnosis of hypertension and type 2 diabetes mellitus were randomly divided into 2 groups and evaluated after 6 weeks of treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…With calcium channel blocker use, the distribution of the relative power over the five frequency bands changed significantly. The majority of the power in the LDF signal lay in the heart beat rather than the LF bands indicating higher pulse wave transmission . Myogenic and neurogenic contributions were suppressed as was that in the respiratory band.…”
Section: Discussionmentioning
confidence: 95%
“…With calcium channel blocker use, the distribution of the relative power over the five frequency bands changed significantly. The majority of the power in the LDF signal lay in the heart beat rather than the LF bands indicating higher pulse wave transmission . Myogenic and neurogenic contributions were suppressed as was that in the respiratory band.…”
Section: Discussionmentioning
confidence: 95%
“…We were also not able to strictly control and exclude hypertensive patients, since hypertension can also cause arteriolar remodeling to a certain extent by means of reactive oxygen species, which may act as a confounder. However, all our hypertensive patients were well‐controlled with antihypertensive medications for more than six months, as reflected by the similarities in systolic blood pressures, which is important since previous studies have shown that the use of antihypertensive medications have the effect of reversing microvascular rarefaction to levels approaching normal values and improving microvascular endothelial function following blood pressure normalization for six months . Otherwise, our study subjects were well matched and homogenously selected, and the reproducibility of the tests was well controlled, with tests being performed by a single operator using a standardized protocol to reduce inter‐ and intra‐observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…¹ Além disso, estudos têm demonstrado que todas as principais classes de medicamentos anti-hipertensivos podem reduzir os resultados cardiovasculares em pacientes com diabetes mellitus, proporcionando benefícios significativos para esses pacientes. 13,14 No entanto, é importante ressaltar que o tratamento ideal deve incluir um bloqueador do sistema renina-angiotensina (IECA ou BRA). Ensaios clínicos baseados em resultados têm indicado que os bloqueadores do sistema renina-angiotensina têm uma eficácia superior em prevenir o aparecimento e a progressão de complicações renais no diabetes, em comparação com outros medicamentos anti-hipertensivos.…”
Section: Diabetesunclassified